2021
DOI: 10.1021/acsenvironau.1c00022
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation─The Other Side of the Mercury Methylation Coin: A Critical Review

Abstract: The public and environmental health consequences of mercury (Hg) methylation have drawn much attention and considerable research to Hg methylation processes and their dynamics in diverse environments and under a multitude of conditions. However, the net methylmercury (MeHg) concentration that accumulates in the environment is equally determined by the rate of MeHg degradation, a complex process mediated by a variety of biotic and abiotic mechanisms, about which our knowledge is limited. Here we review the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 227 publications
(721 reference statements)
2
45
1
Order By: Relevance
“…2d). The decrease in MeHg concentrations could be partially attributed to potential demethylation in the soil, as previously reported (Barkay and Gu, 2021;Bridou et al, 2011;Hamelin et al, 2015;. This conclusion is supported by additional experiments incubating both the fen and bog soils with isotopically labeled Me 202 Hg.…”
Section: Methylmercury Production In the Bog Soil And Comparisons Wit...supporting
confidence: 85%
“…2d). The decrease in MeHg concentrations could be partially attributed to potential demethylation in the soil, as previously reported (Barkay and Gu, 2021;Bridou et al, 2011;Hamelin et al, 2015;. This conclusion is supported by additional experiments incubating both the fen and bog soils with isotopically labeled Me 202 Hg.…”
Section: Methylmercury Production In the Bog Soil And Comparisons Wit...supporting
confidence: 85%
“…53,54 In contrast, MMHg demethylation can be mediated biotically by a broad array of aerobic and anaerobic microorganisms or by abiotic reactions. 12,55,56…”
Section: Discussionmentioning
confidence: 99%
“…53,54 In contrast, MMHg demethylation can be mediated biotically by a broad array of aerobic and anaerobic microorganisms or by abiotic reactions. 12,55,56 Hg methylation within algal biolms (periphyton) in EFPC is an important process exerting control on the diel oscillations in MMHg D concentration. Several investigators have reported net positive MMHg generation by algal biolms.…”
Section: Controls On Dissolved Hg and Mmhg Concentrationsmentioning
confidence: 99%
“…Biological MeHg demethylation and Hg 2+ reduction detoxification processes can be mediated by different biotic processes, including reductive reactions mediated by the mer operon, 30,31 but also oxidative reactions 32,33 as well as the recently described MeHg degradation performed by methanotrophic bacteria. 34 In this article, we will focus only on the study of bacteria carrying the mer operon (i.e., biological reductive MeHg degradation pathways). While the operon can be composed of different sets of genes, 30,31 the key genes are merA and merB.…”
Section: ■ Introductionmentioning
confidence: 99%